The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1038/srep41208
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Microfluidic Flow-Through Microbial Fuel Cells

Abstract: This paper reports on a miniaturized microbial fuel cell with a microfluidic flow-through configuration: a porous anolyte chamber is formed by filling a microfluidic chamber with three-dimensional graphene foam as anode, allowing nutritional medium to flow through the chamber to intimately interact with the colonized microbes on the scaffolds of the anode. No nutritional media flow over the anode. This allows sustaining high levels of nutrient utilization, minimizing consumption of nutritional substrates, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 55 publications
0
21
1
Order By: Relevance
“…The feasibility of using graphene foam as an anode was also investigated. It was found that a graphene foam anode has increased electrochemical interactions and results in reducing bio-convertible substrate consumption, while maintaining a short response time [68].…”
Section: Mfc-derived Bioelectrochemical Cells In Particular Mecs (Mimentioning
confidence: 99%
“…The feasibility of using graphene foam as an anode was also investigated. It was found that a graphene foam anode has increased electrochemical interactions and results in reducing bio-convertible substrate consumption, while maintaining a short response time [68].…”
Section: Mfc-derived Bioelectrochemical Cells In Particular Mecs (Mimentioning
confidence: 99%
“…These structures help the mass transport by forming water channels. These cracks were also observed with the Shewanella oneidensis MR-1 biofilm grown on gold by Qian et al [ 8 ] and on graphene foam by Jiang et al [ 45 ]. These voids also lead to imperfect contact between the bacteria and the gold surface, causing a decrease in the electrical conductivity of the biofilm matrixes, which lowers the performance of the fuel cell, as suggested by other studies [ 49 , 50 , 51 ].…”
Section: Resultsmentioning
confidence: 64%
“…Bacteria usually prefer to adhere to carbon-based materials, but they are difficult to integrate in MEMS processes compared to gold as an electrode material. There are studies being conducted to adapt carbon-based electrodes to micro-scale MFCs [ 45 ], but their fabrication is not yet compatible with mass production solutions.…”
Section: Resultsmentioning
confidence: 99%
“…11 Jiang et al proposed a ow-through mMFC using 3D graphene foam as an anode, which had an estimated internal resistance of 7.3 kU. 12 Recently, micro MFCs without membranes, also called laminar-ow microbial fuel cells (LFMFCs), have attracted much attention, which contain a virtual barrier controlled by the co-laminar ow to separate the anolyte and catholyte. [13][14][15][16][17] The membrane-less structure can reduce both the fabrication cost and the internal resistance of the fuel cell.…”
Section: Introductionmentioning
confidence: 99%